Writing the Teaching System of Religious Adherents; Assistance to the Indigenous People of the Anak Rawa Siak Tribe of Riau Province - Sukiyat Sukiyat; Suja’i Syarifandi; Masbukin Masbukin; Imam Hanafi (Kutubkhanah, 2025)
This community service activity aims to document the Religious Teaching System of the Anak Rawa Indigenous People as a strategic step to obtain legal recognition and preserve the cultural heritage of their ancestors. Using a Participatory Action Research (PAR) approach, this activity involves the active participation of the community in every stage, from problem identification and joint strategy development to assistance in the book writing process. The community service team and the community held focus group discussions and in-depth interviews to collect data and strengthen the capacity of the local community. The results of the activity show that the teachings and belief system of the Anak Rawa Indigenous People not only contain spiritual values, but also reflect a harmonious relationship with the environment, social solidarity, and respect for ancestors. The documentation in the form of a book has become a symbol of identity as well as an instrument of advocacy for legal recognition.